Glucocorticoid use and perceptions of side effects among patients with rheumatic medical diseases: Insights from a developing country - Fatima Alnaimat; Hamza Alduraidi; Ali Rezeq Ali Yaghi; Mohammad Mahmoud Tarbiah; Asim Khanfar; Moath Abusheikha; Ali M. Hamad (PLoS ONE, 2025)
Chronic glucocorticoid (GC) therapy is common in patients with rheumatic medical diseases (RMD). However, long-term use of GCs can be associated with significant adverse effects. This study aims to determine the prevalence of GC use among patients with RMD and understand their perceptions of GC use and safety. This cross-sectional survey was conducted at a tertiary academic university hospital in Amman, Jordan. RMD patients were anonymously approached while awaiting rheumatology clinic appointments. Convenience sampling was employed, with enrollment taking place between January and September 2021. Of 500 participants, 315 (63%) reported current (171/315, 54.3%) or past (144/315, 45.7%) use of GCs, primarily prescribed for RMD (267/315, 84.7%). Most (270/315, 85.7%) used GCs orally, with the majority taking them daily (266/315, 84.4%). A small percentage (33/315, 10.5%) used GCs only as needed. Long-term use was common, with 57.8% (182/315) reporting use for years and 84.1% (265/315) adhering to doctor recommendations. Perception-wise, 69.5% (219/315) of GC users believed in its efficacy, whereas 78.7% (248/315) considered it unsafe, compared to 51.9% (96/185) of non-users. Awareness of side effects was higher among GC users (219/315, 69.5%) than non-users (79/185, 42.7%), with weight gain being the most reported side effect. Media and personal research were the primary information sources for GC users (193/315, 61.3%). Side effects were reported by 110/315 (34.9%) GC users, with weight gain as the most common (47%). Both perceived efficacy and safety of GC were positively and significantly correlated with educational level (p = .005, p = .000, respectively) and monthly income (p = .044, p = .000, respectively). GC use is prevalent among Jordanian patients with RMDs, with perceptions of efficacy and safety strongly influenced by education and income. Enhanced patient education on the side effects of GC is crucial for improving treatment adherence and outcomes.